2000
DOI: 10.1590/s0004-28032000000400005
|View full text |Cite
|
Sign up to set email alerts
|

HCV infection in northeastern Brazil: unexpected high prevalence of genotype 3a and absence of African genotypes

Abstract: -The genomic diversity of HCV embraces 6 genotypes and at least

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
4
13
0
6
Order By: Relevance
“…In the present study, the most frequent genotype was genotype 1 (84% of infected patients), as also observed in several other geographic regions of Brazil (33)(34)(35)(36)(37)(38). The fact that genotype 1b was more frequent in the present study placed these patients in the group of individuals with the worst response to currently available antiviral treatment (13)(14)(15)(16)(17), who are likely to be assigned to the group of pegylated interferon monotherapy since the use of ribavirin is contraindicated (17,39).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the most frequent genotype was genotype 1 (84% of infected patients), as also observed in several other geographic regions of Brazil (33)(34)(35)(36)(37)(38). The fact that genotype 1b was more frequent in the present study placed these patients in the group of individuals with the worst response to currently available antiviral treatment (13)(14)(15)(16)(17), who are likely to be assigned to the group of pegylated interferon monotherapy since the use of ribavirin is contraindicated (17,39).…”
Section: Discussionsupporting
confidence: 90%
“…Genotype 1 is the most prevalent worldwide, followed by genotypes 3 and 2 (Sablon & Shapiro 2004). In most Brazilian regions, genotype 1 is the etiologic agent in 60-75% of HCV infections (Paraná et al 2000, Campiotto et al 2005. Genotype 3 is the second-most prevalent strain and genotype 2 constitutes less than 5% of cases.…”
mentioning
confidence: 99%
“…A distribuição dos genótipos HCV em mono-infectados da região de Botucatu segue o mesmo padrão do Estado de São Paulo 26 e de outros estados brasileiros [27][28][29] , ou seja, uma maior freqüência do genótipo 1 seguido pelos 3 e 2, observando-se também a presença dos genótipos 5 26,27,30 . Comparando-se a freqüência dos genótipos HCV entre pacientes mono e co-infectados verificamos que nos co-infectados houve um aumento de 10% no genótipo 1, uma queda de 7,7% do genótipo 3 e ausência de outros genótipos.…”
Section: Tabela 1 -Distribuição Dos Genótipos E Subtipos Virais Em Paunclassified